Videos using different message strategies to promote the interruption of sedentary behavior in university students during online lectures - A pilot study - Anastasia Doré; Kristin Kalo; Lisa Schwab; Jennifer L. Reichel; Laura Eisenbarth; Tilmann Strepp; Robin Jacob; Kira Enders; Stephan Letzel; Perikles Simon; Pavel Dietz; Thomas Kubiak; et al. (Frontiers Media S.A., 2023)
BackgroundSedentary behavior (SB) is highly prevalent among university students and has increased during COVID-19 pandemic. As SB is associated with negative health outcomes, appropriate prevention measures in the university setting are needed.ObjectiveThis pilot study aimed at investigating the effects of videos using different message strategies to interrupt SB in the collective of university students during online lectures.MethodsDuring online lectures, university students (N = 96) were shown one of three videos on the interruption of SB. The videos differed in their message strategies with regard to evidence type (statistical vs. narrative) and vividness (static vs. animated images). Demographics, health variables (SB intentions, SB attitudes) and selected media reception variables (identification, homophily, counterarguing) were examined as possible influence factors on the interruption of SB evoked by watching the video.ResultsApproximately half of the students interrupted sedentary behavior during watching the videos and students of the older age group (cut-off: median = 22 years) interrupted SB significantly more often (p = 0.046). The interruption of SB was predicted by SB intentions (p < 0.05). Identification with characters significantly predicted the intentions to reduce SB (p < 0.001), with a large effect of the overall regression model (R2corr = 0.47).ConclusionConsidering the increased digitalization in general and restrictions due to COVID-19 pandemic, videos seem to be a useful tool to interrupt SB among university students during online lectures. Narrative formats could facilitate the intention to reduce SB, which in turn could have a positive impact on the interruption of SB. However, further research on effective communication and message strategies is needed.